DEVELOPMENT OF THE INTELLECTUAL POTENTIAL OF PROCESSING ENTERPRISES AS A COMPONENT OF INCREASING COMPETITIVENESS - PALIANYTSIA, Stanislav (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the conditions of globalization and rapid technological progress, the development of the intellectual potential of processing enterprises becomes especially relevant. Intellectual potential, which includes knowledge, skills, innovative approach and creative abilities of employees, is a key factor in the successful adaptation of enterprises to changing market conditions and increasing their competitiveness. It is the ability to innovate and constantly improve production processes that determines how effectively a company will be able to compete in the international arena. The purpose of this study is to analyze the meaning and ways of developing the intellectual potential of processing enterprises as a key factor in increasing their competitiveness. Particular attention is paid to the study of modern trends in the field of human resources management, the evaluation of the effectiveness of investments in the development of intellectual potential, and the development of recommendations for the implementation of best practices in the activities of Ukrainian processing enterprises. Processing enterprises, given their specificity, have significant potential for innovation and process optimization through the development of intellectual resources. Investments in education and training of personnel, stimulation of scientific and research activities and creation of a favorable environment for creative self-realization are becoming critically important elements of the development strategy. The introduction of the latest technologies, the automation of production processes and the active use of digital solutions make it possible to increase the productivity and quality of products, which in turn contributes to the strengthening of competitive positions on the market. The development of the intellectual potential of processing enterprises is a fundamental aspect of their competitiveness in the global economy. Intellectual potential, which includes the knowledge, skills, innovative approach and creativity of employees, plays a decisive role in providing enterprises with the ability to respond effectively to rapid market changes, implement new technologies and optimize production processes. The study of modern trends in the field of human resources management shows that successful enterprises actively invest in the training and development of their employees, stimulate innovative initiatives and create a favorable corporate culture. Digitization, flexibility of working conditions, a strategic approach to human resource management and the development of emotional intelligence of managers are key factors that contribute to increasing productivity and product quality. Therefore, a strategic focus on the development of intellectual potential is key for processing enterprises seeking to achieve long-term success and sustainable development. Investments in education, innovation and the formation of a positive corporate culture contribute not only to increasing the efficiency of the enterprise, but also to its stable growth and strengthening of competitive positions in the global market.
Keywords: intellectual capital; intellectualization; development; strategic development; entrepreneurship; human resources; labor potential; processing enterprises